Ecology of siliceous sponges - Application to the environmental interpretation of the Upper Jurassic sponge facies (Oxfodian) from Spain. - Krautter, M. (Cuadernos de Geología Ibérica, 1998)
the major factors controtling [he morphological and taxonomie composition of siliceous sponge faunas are sedimentation rate and nutrient supply. In seawater bacteria are most abundant in the upper par[ of [he water column. Towards greater depths bacteria disappear gradually. The bathymetric distribution of filter-feeding sponges (demosponges mcl. lithistid demosponges) is consequently linked to the distribution of bacteria, their food. Sponge associa[ions consisting exclusively of hexactinosan sponges clearly demonstrate [he absence of sufficient free bacteria. The tissue organisation of hexactinellids allows [bern to absorb coloidal organic mauer or dissolved amino acids, which represents [heir predorninant feeding strategy. If [bis type of food is scarce, hexactinellid.s tend lo reduce wafl thickness which improves [heir overail contad with sea water. Moreover, morphovariable taxa enlarge their surface by developing thin plate- or dish-shaped forms. Arnong morphostable taxa dish-shaped forms have an adaptional advantage in [hese settings and will outcornpete other forms. Reduced sedimentation rate is a general precondition for [he establishrnent of sponge communities, aLthough sorne sponges can adapt [o a certain degree of sedimentation. Slighdy elevated rates of sedimentation favour tube-shaped sponges, since a narrowed osculum produces a bundied exhalant water current whicb shelters [be animal from [he settlement of sediment particles. Sin 223 Eeologv of siliccoas spon ges - Applñation te the environmental. Manfred Kraatter ce changes in sedimentation are accompanied by changes in tbe influx of nutrients, the sedimentation rate directly or indireetly influences the sponges. Sedimentation therefore represents a prime factor controlling morphological as well as taxonomie dominanee and diversity of siliceous sponge faunas. TEe siliceous sponge fauna of the Yátova Formation of eastem Spain cíearly demonstrates thai the shape of morphovariable sponges as well as the taxonomic composition of rnorphostable sponges mirror external environmental factors. The reduced sediment intiux is iníerpreted to bave resulted in a very 10w nutrient level, whieh is reflected by a strong reduction in filter-feeding organisms frequent in other Late Jurassic sponge settings. The sponge fauna itself is characterized by the almost exclusive oceurrence of a uniform, low-diversity but abundant fauna of bexactinosan dish-sbaped sponges, uncommon in most other Late Jurassic sponge faunas. Llíhistid demosponges only play a minor role.